Voltage and reactive power correlation in multi-objective optimization of an offshore grid - Muhammad Raza (Taylor & Francis Group, 2021)
In the last few years, many offshore wind power plants are installed at North Sea and more are under construction. Offshore grid would be vital in the integration of future offshore wind power plant with the main land grid. Both, multi-terminal DC and AC cable systems are under consideration in the concept of future offshore grid. The reactive power and voltage operating point for such a network is important for the optimized operation. This article presents an optimization criterion of voltage and reactive power control for an offshore AC grid having a parallel connecting grid-forming converter. Multi-objective optimization problem is formulated considering four reactive power management strategies. The solution of the optimization algorithm is analysed and compared with respect to active power losses in the network, voltage variation, and reactive power contribution by the sources. The research presents a methodology to apply a suitable reactive power management strategy to achieve the best optimum operating points. The solution provides the optimum operating points for offshore wind farm reactive power, frequency and voltage droop gain values for VSC-HVDC system, and reactive power sharing factor of HVDC transmission.